The effectiveness of a school-based, universal mental health programme in six European countries - Cefai, Carmel; Camilleri, Liberato; Bartolo, Paul; Grazzani, Ilaria; Cavioni, Valeria; Conte, Elisabetta; Ornaghi, Veronica; Agliati, Alessia; Gandellini, Sabina; Tatalovic Vorkapic, Sanja; Poulou, Maria; Martinsone, Baiba; et al. (Frontiers in Psychology, 2022)
As children and young people today face ever increasing social, emotional and mental health challenges, schools, as one of the primary systems in children’s lives, are called to broaden their agenda and help to address these challenges. This paper discusses the evaluation of a school- based, universal mental health promotion programme developed recently for the European context. The programme provides a universal curriculum from early years to high school, aiming to promote social and emotional learning and resilience and prevent risk behaviours in children and adolescents. A total of 7789 students (and their teachers and parents) from kindergarten to high school across 6 countries in Europe were recruited from 434 classrooms in 124 schools in 6 countries, making use of cluster sampling. A quasi-experimental longitudinal design was used to evaluate the impact of the programme on students’ outcomes by comparing the groups' outcomes within times (pre-test vs post-test) and between groups (experimental vs control group). A total of 779 classroom teachers completed pre and post scales measuring students’ social and emotional learning, mental health and academic achievement. Results indicate that the experimental group had significantly larger pre-post increase in social and emotional competence and prosocial behaviour, and a decrease in mental health issues (externalising and internalising problems). No significant impact was found for academic achievement. The findings are discussed in view of the limitations of the study and areas for further research.